Over the top or endobutton for ACL reconstruction? - Verdano, M.A.; Pedrabissi, B.; Lunini, et al., E. (Acta Biomedica Atenei Parmensis, 2012)
There are an estimated 80-100,000 ACL repairs in the US each year: most ACL tears occurs from noncontact injuries. The 3.9% of the knee ligament injuries undergoes surgery: in the 80% of these patients, this means ACL reconstruction. The purpose of this study is to compare two surgical techniques normally used for acl recustruction; the first one is the intra- extra articular technique with single bundle fixed with staples and the second one is the intra-articular technique with double bundle and endobutton post-fixation. We evaluate the clinical outcome of our patients at the time of 4 years follow up. From January 2006 to April 2009 40 patients underwent to ACL reconstruction, all operated by using hamstring tendons: 20 patients with an average age of 28,75 years (12 men and 8 women) underwent surgery using the intra-extra articular technique, whereas the remaining 20 patients with an average age of 34,5 years (11 men and 9 women) benefited the intra-articular technique with double bundle ligament and endobutton post-fixation. Our study shows no substancial difference between these two technique, but clinical outcome measures (I.K.D.C., Lysholm and Tegner) estimated better results for the double bundle technique with Endobutton post-fixation.